The Social, Cognitive and Socio-Demographic Profile of Potentially Gifted Children - Klarin, Mira; Šimić Šašić, Slavica; Proroković, Ana (Revija za elementarno izobraževanje, 2023)
The research results suggest that teachers find potentially gifted children to be academically more competent and sociable as opposed to students without the same potential. Likewise, potentially gifted children tend to have better academic achievements. When it comes to their socio-demographic profile, there seem to be more female students than male, and they often live in urban areas. Additionally, both parents of potentially gifted children show higher levels of education when compared to parents of non-potentially gifted children. The results of the hierarchical regression analysis point to significant effects by gender, place of residence and parental education have in explaining children’s academic competence and sociability; results also reveal significant incremental validity in the assessment of cognitive ability, motivation, and creativity.
Keywords: giftedness, academic competence, sociability, gender, parental education